Dynamics of the charged particles in a field of intensive electromagnetic waves - Buts, V.A.; Kuzmin, V.V. (Вопросы атомной науки и техники, 2007)
The results of the investigations of the charged particles dynamics in field of intense electromagnetic waves and electromagnetic impulse are represented. It was shown, that the traditional scheme of the acceleration, such as inverse free electron laser in such fields are not efficiently. Accelerating particles by laser impulse allows to all accelerated particles to have absolutely identically trajectories. The limitation on maximum energy, which particles can received and which is caused by radiation friction are removed. Наведено результати досліджень динаміки заряджених часток у полі інтенсивних електромагнітних хвиль й електромагнітних імпульсів. Показано, що традиційна схема прискорення типу зверненого лазера на вільних електронах у таких полях мало ефективна. При прискоренні заряджених часток лазерним імпульсом всі прискорені частки, можуть рухатися абсолютно ідентично. Знято обмеження на гранично можливі значення енергії прискорених часток при лазерному прискоренні, які обумовлені радіаційним тертям. Изложены результаты исследований динамики заряженных частиц в поле интенсивных электромагнитных волн и электромагнитных импульсов. Показано, что традиционная схема ускорения типа обращенного лазера на свободных электронах в таких полях мало эффективна. При ускорении заряженных частиц лазерным импульсом все ускоряемые частицы могут двигаться абсолютно идентично. Сняты ограничения на предельно возможные значения энергии ускоряемых частиц при лазерном ускорении, которые обусловлены радиационным трением